EDUKASI PEMANFAATAN TANAMAN HERBAL DALAM MENGOBATI PENYAKIT YANG SERING TERJADI DI MASYARAKAT - Nurani Puspa Ningrum; Heni Risnawati; Hasriyani Hasriyani; Yulisetyaningrum Yulisetyaningrum; Widya Cholid Wahyudin (Universitas Muhammadiyah Kudus, 2023)
Abstract Hypertension, cholesterol, gout and ARI are diseases that often infect the community. High blood pressure is what causes hypertension. This increases the chance of heart disease and stroke as well as other health problems. The body makes cholesterol from fats found in animal products. Due to the presence of uric acid crystals, gout conditions cause joint pain or inflammation. Infections that attack the respiratory tract and are caused by viruses are called acute respiratory infections or ARI. The service technique is carried out through lectures and discussions about diseases that often attack the surrounding environment and the use of medicinal plants in nature. It is hoped that the public will become more familiar with various diseases, including hypertension, cholesterol, gout and ARI, use herbal plants to cure these diseases, and become more concerned about their own health as a result of service activities. Kata Kunci: Hypertension, Cholesterol, Uric Acid, ARI